Does Sharia Supervisory Board Size and Rotation Affect Islamic Banking in Asia Oic Countries Compliance? Measured By The Maqashid Sharia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study evaluates the influence of the size and rotation of the Sharia Supervisory Board (SSB) on the Maqashid Sharia Performance (MSP) in Islamic banks in 12 member countries of the Organization of Islamic Cooperation (OIC) in Asia. Using data from 49 Islamic banks during the 2021-2023 period accessed through annual reports, the analysis was carried out using a Random Effect Model (REM). Independent variables include SSB size, which is measured by the number of members, and SSB rotation, which is assessed based on member turnover in a year. MSP is measured using the Maqashid Sharia Index with the Abu Zahrah approach involving the dimensions of education, community welfare, and public interest. The results showed that the size and rotation of SSB did not have a significant influence on MSP. These findings indicate weaknesses in Islamic banking governance in OIC member countries, including a suboptimal SSB recruitment system and a lack of effective supervision from high-level Islamic authorities. In addition, the contribution of independent variables to MSP performance is considered low, so it is concluded that other factors, such as SSB experience, sharia internal control system, and regulatory policies, can have a more significant influence.